Aplikasi Media Pembelajaran Tumbuhan Langka Indonesia menggunakan Augmented Reality berbasis Android - Saepul Reza Alparizi; Sutarman Sutarman (Universitas Hamzanwadi, 2023)
The absorption and understanding of grade 2 students at SDN SINDUADI 1 in learning about rare plants is still lacking, resulting in students having little or no knowledge of Indonesia's rare plants. Using smartphones as a learning medium is an example of utilizing today's technology. The use of technology in education supports teachers and students in creating creative, innovative, educational, and interactive learning activities. The aim of this research is to create learning media using augmented reality technology to increase students' absorption, understanding, and interest in learning about rare Indonesian plants. This research uses the research and development method to develop products and test their level of effectiveness. System development uses the waterfall SDLC (Software Development Life Cycle) model, including requirements analysis, modeling, implementation, testing, and maintenance stages. Data collection was done through literature study techniques, observation, and questionnaires. Application testing in this research used an alpha test by us and a beta test in the form of a questionnaire using a random sampling technique carried out by nine user samples taken from 30% of the population. The results of this research show that combining augmented reality technology with educational games can support students' absorption and understanding of learning about rare Indonesian plants. Indonesian rare plant learning media shows the feasibility of the media, getting a score of 95.6%. Based on the Likert scale test results, it was concluded that the application for learning rare Indonesian plants using AR technology was very suitable for use.